Activation of GRP78 ATPase suppresses A549 lung cancer cell migration by promoting ITGB4 degradation. Issue 1 (31st December 2022) - Ning, Junya; Cui, Xiaoling; Li, Nan; Li, Na; Zhao, Baoxiang; Miao, Junying; Lin, Zhaomin
ABSTRACT: Hypochlorous acid (HOCl) is an essential signal molecule in cancer cells. Activated GRP78 ATPase by a HOCl probe named ZBM-H inhibits lung cancer cell growth. However, the role and underlying mechanism of GRP78 ATPase in lung cancer cell migration have not been established. Here, we reported that activation of GRP78 ATPase by ZBM-H suppressed A549 cell migration and inhibited EMT process. Notably, ZBM-H time-dependently decreased the protein level of integrin β4 (ITGB4) in A549 cells. Combinatorial treatment of 3BDO (an autophagy inhibitor) and ZBM-H partially rescued the protein level of ITGB4. Consistently, 3BDO partially reversed ZBM-H-inhibited cell migration. Furthermore, ZBM-H promoted the interaction between ANXA7 and Hsc70, which participated in the regulation of selective autophagy and degradation of ITGB4.